Whole-genome resequencing of native and imported dairy goat identifies genes associated with productivity and immunity - Zhao, Jianqing; Mu, Yuanpan; Gong, Ping; Liu, Baolong; Zhang, Fuhong; Zhu, Lu; Shi, Chenbo; Lv, Xuefeng; Luo, Jun (Frontiers in Veterinary Science, 2024)
Understanding the differences in genetic variation between local Chinese dairy goat breeds and imported breeds can help germplasm innovation and molecular breeding. However, the research is limited in this area. In this study, whole-genome resequencing data from 134 individuals of both local and imported dairy goat breeds were analyzed, and their differences in genomic genetic variation, genetic diversity, and population structure were subsequently identified. We also screened candidate genes associated with important traits of dairy goats such as milk production (STK3, GHR, PRELID3B), reproduction (ATP5E), growth and development (CTSZ, GHR), and immune function (CTSZ, NELFCD). Furthermore, we examined allele frequency distributions for the genes of interest and found significant differences between the two populations. This study provides valuable resources for the study of genetic diversity in dairy goats and lays the foundation for the selective breeding of dairy goats in the future.